Maternal psychological distress and visitation to the neonatal intensive care unit. (27th February 2015) - Greene, Michelle M.; Rossman, Beverly; Patra, Kousiki; Kratovil, Amanda; Khan, Samah; Meier, Paula P.
Abstract Aim To examine associations between maternal neonatal intensive care unit (NICU) visitation rates, maternal psychological distress ('distress') and preterm infant outcome post‐NICU discharge in a contemporary cohort of very low birthweight (VLBW) infants. Methods This was a prospective study of 69 mothers and their VLBW infants. Distress was assessed 1‐month postbirth, 2 weeks prior to NICU discharge and after NICU discharge at 4‐month corrected age (CA). Maternal NICU visitation rates were calculated for the first 2 weeks and 1‐month postbirth as well as for the entire NICU hospitalization. Regression analyses adjusted for the impact of (i) maternal and infant characteristics and distress on maternal visitation rates and (ii) the impact of visitation on long‐term maternal distress and rates of infant clinic attendance and rehospitalization. Results Greater number of children in the home, maternal exposure to a greater number of potentially traumatic events prior to childbirth and lower maternal anxiety consistently predicted lower visitation rate. Lower maternal visitation rate predicted higher maternal depression scores at infants' 4‐month CA visit. Maternal NICU visitation rate did not predict post‐NICU discharge infant clinic attendance or rehospitalization. Conclusion Distress is an important predictor of visitation. In turn, visitation is associated with long‐term maternal distress.